Chitosan particles agglomerated scaffolds for cartilage and osteochondral tissue engineering approaches with adipose tissue derived stem cells - Malafaya, P. B. (2005)
It is well accepted that natural tissue regeneration is unlikely to occur if the cells are not supplied with an extracellular matrix (ECM) substitute. With this goal, several different methodologies have been used to produce a variety of 3D scaffolds as artificial ECM substitutes suitable for bone and cartilage tissue engineering. Furthermore, osteochondral tissue engineering presents new challenges since the combination of scaffolding and co-culture requirements from both bone and cartilage applications is required in order to achieve a successful osteochondral construct. In this paper, an innovative processing route based on a chitosan particles aggregation methodology for the production of cartilage and osteochondral tissue engineering scaffolds is reported. An extensive characterization is presented including a morphological evaluation using Micro-Computed Tomography (μCT) and 3D virtual models built with an image processing software. Mechanical and water uptake characterizations were also carried out, evidencing the potential of the developed scaffolds for the proposed applications. Cytotoxicity tests show that the developed chitosan particles agglomerated scaffolds do not exert toxic effects on cells. Furthermore, osteochondral bilayered scaffolds could also be developed. Preliminary seeding of mesenchymal stem cells isolated from human adipose tissue was performed aiming at developing solutions for chondrogenic and osteogenic differentiation for osteochondral tissue engineering applications.